Shape and drilling technology of semi-precious stone beads in National Museum Somdet Phra Narai, Lopburi - Chaipipat Pokpong; Wannaporn Reanjang (Asian Creative Architecture, Art and Design : ACAAD, 2025)
This article aims to investigate the shapes and drilling technologies of semi-precious stone beads that are displayed in Somdet Phra Narai National Museum, Lopburi. Three types of semi-precious stone beads are inspected: 1) carnelian beads, 2) agate beads and 3) greenstone beads. The methods carried out for the inspection include making silicone impressions of the drill holes of the beads and examining them under scanning electron microscope. The identification of drilling technologies is supported by comparisons between drill holes of beads during early Historic period in South Asia. The result shows that the carnelian and agate beads share similar shapes and drilling technique to carnelian and agate beads that were found in South Asia contemporary to the Iron age in Thailand, which was approximately 1500-2500 years ago. On the other hand, most greenstone beads show different shapes and drilling technique. Such differences may suggest that different workshop traditions. This study reveals data that have hitherto not been investigated. The resulting data can be used as a database for work related to ancient stone beads in Thailand.
Keywords: 3D Surveying and Cultural Heritage